Council-managed personal budgets for older people: Improving choice through market development and brokerage?. (December 2013) - Baxter, Kate; Rabiee, Parvaneh
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents findings from interviews with social care service development managers and brokers in three local authorities. It follows an earlier study exploring choice and flexibility in home care services for older people using council-managed personal budgets. That study found that local authorities were limiting the number of providers on framework agreements for home care services so that there were sufficient to encourage competition but not so many that providers risked having insufficient business to remain financially viable. It also found that communication issues were affecting the proper functioning of brokerage systems. The current study therefore revisited the same three local authorities to investigate changes in framework agreements and developments in brokerage systems. The findings showed little change in the number of providers on framework agreements and remaining communication challenges for brokers. However, lessons had been learned from unforeseen consequences of framework agreements, and progress was being made towards encouraging market development and diversification of service provision.